Masters of Disasters? An Empirical Analysis of How Societies Benefit from Corporate Disaster Aid - Ballesteros, Luis; Useem, Michael; Wry, Tyler (Academy of Management Journal, 2017)
Corporations are increasingly influential within societies worldwide, while the relative capacity of national governments to meet large social needs has waned. Consequentially, firms face social pressures to adopt responsibilities that have traditionally fallen to governments, aid agencies, and other types of organizations. There are questions, though, about whether this is beneficial for society. We study this in the context of disaster relief and recovery, in which companies account for a growing share of aid, as compared to traditional providers. Drawing on the dynamic capabilities literature, we argue that firms are more able than other types of organizations to sense areas of need following a disaster, seize response opportunities, and reconfigure resources for fast, effective relief efforts. As such, we predict that, while traditional aid providers remain important for disaster recovery, relief will arrive faster and nations will recover more fully when locally active firms account for a larger share of disaster aid. We test our predictions with a proprietary data set comprising information on every natural disaster and reported aid donation worldwide from 2003 to 2013. Using a novel, quasi-experimental technique known as the “synthetic control method,” our analysis shows that nations benefit greatly from corporate involvement when disaster strikes.